841. ILEX DIMORPHOPHYLLA: Aquifoliaceae. (September 2016) - Nagamasu, Hidetoshi
Summary: The holly, Ilex dimorphophylla Koidz., an endangered endemic from the Ryukyu Islands, is illustrated and described. The habit of leaf dimorphy, between spiny and spineless leaves, is discussed.